INTEGRASI ARTICULATER STORYLINE DALAM MOBILE LEARNING: ANALISIS KEBUTUHAN BAHAN AJAR AUDIO VISUAL PADA MATAKULIAH TENIS LAPANGAN - Septian Raibowo; Joan Siswoyo; Indri Wulandari; Rices Jatra (YLPK Mahardhika, 2026)
This study aims to analyze the need for developing audio-visual teaching materials based on Articulate Storyline to support the implementation of mobile learning in a tennis course. The study employed a descriptive quantitative approach using a survey method. The subjects were 120 students from the Physical Education Study Program who had taken or were currently enrolled in the tennis course. The research instrument was a questionnaire developed based on indicators including learning conditions, students’ initial abilities, facilities and infrastructure, utilization of learning resources, and the need for Articulate Storyline-based teaching materials. The results showed that the learning process is still dominated by conventional methods with limited use of digital media. A total of 88.33% of students had low basic tennis skills, and 75% had no prior learning experience. However, 100% of students owned smartphones and 95% had stable internet access, indicating a high level of readiness for mobile learning implementation. Furthermore, 91.67% of students expressed a strong need for interactive audio-visual teaching materials accessible via mobile devices. Based on these findings, the integration of Articulate Storyline into mobile learning is considered a relevant solution for developing interactive, flexible, and effective teaching materials to improve the quality of tennis learning